2018
DOI: 10.1016/j.jcmgh.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Variability Promotes Both Local Invasion and Metastatic Colonization by Pancreatic Ductal Adenocarcinoma

Abstract: Background & AimsAlthough nearly half of pancreatic ductal adenocarcinoma (PDAC) patients have diabetes mellitus with episodes of hyperglycemia, its tumor microenvironment is hypoglycemic. Thus, it is crucial for PDAC cells to develop adaptive mechanisms dealing with oscillating glucose levels. So far, the biological impact of such glycemic variability on PDAC biology remains unknown.MethodsMurine PDAC cells were cultured in low- and high-glucose medium to investigate the molecular, biochemical, and metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…However, our findings did not indicate a significant association between local lymph node metastasis and COL6A1 expression. In line with studies reporting a positive relationship between COL6A1 and distant metastasis (36), we found that 73.1% of COL6A1 + patients had distant metastasis. Also, 76.9% of our patients with COL6A1 expression had vascular encroachment at the time of surgery.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, our findings did not indicate a significant association between local lymph node metastasis and COL6A1 expression. In line with studies reporting a positive relationship between COL6A1 and distant metastasis (36), we found that 73.1% of COL6A1 + patients had distant metastasis. Also, 76.9% of our patients with COL6A1 expression had vascular encroachment at the time of surgery.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have detected increased expression of COL6A1 in tumors and is associated with tumor progression (36,37). Other reports have also shown that collagen VI can promote the adhesion, penetration and invasion of tumor cells in an autocrine manner (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high-glucose environment without glycemic pretreatment triggers an invasive character with an elevation in pERK expression in pancreatic cancer cells [32,33]. When incubated for more than 4 weeks in high-or low-glucose medium, high-glucose medium-pretreated Kras-mutant pancreatic cancer cells show an enhanced metastatic ability, while low-glucose medium-maintained cells show a stronger tendency toward local invasion [34]. In our study, 72-hr incubation in a low-or high-glucose medium produced no changes in cell viability or sphere formation; however, after 28 days of pretreatment, the cell characteristics dramatically changed, with the promotion of cell proliferation and tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…RUNX3 expression has been associated with mothers against decapentaplegic homolog 4 (SMAD4, also known as DPC4) copy number variants, and level patterns have been directly associated with relapse and the response to therapies (160). RUNX3 expression has also been associated with combined epigenetic programs and metabolic processes when it is part of the retinoic acid receptor β/RUNX3/collagen α-1(VI) chain signal axis, linking hypoglycemia with local invasion and angiogenesis, and hyperglycemia with metastatic colonization (162).…”
Section: Runx Regulatory Rolementioning
confidence: 99%